Christian Thought in America : A Brief History - Schell, Hannah; Ott, Daniel (Book collections on Project MUSE., 2015)
In Christian Thought in America: A Brief History, Daniel Ott and Hannah Schell offer a short, accessible overview of the history of Christian thought in America, from the Puritans and other colonials to the beginning of the twenty-first century. Moving chronologically, each chapter addresses a historical segment, focusing on key movements and figures and tracing general trends and developments. While many texts offer a detailed history of Christianity in the American context, few focus on the philosophical and theological issues, which form an important yet often neglected part of our history. The narrative aims to underscore the diversity of Christian thought in America by addressing issues in their historical contexts and by examining across a range of traditions. At the same time, it conveys a sense of the vibrancy of Christian thought, as well as the liveliness and creativity of the ongoing theological debates. The book explores several recurring themes that mark the trajectory of Christian thought in America, including the idea of a divine mission, the tendency to privilege the individual, and the influence of the spirit of reform and revival. Each chapter concludes with a short bibliograpy of recent scholarship for further reading.